Model Pendidikan Keluarga Dalam Perspektif Al-Qurâan - Basyir, Abd (IAIN Antasari Banjarmasin, 2015)
There are two models of family education in view of the Al-qurâan. First, the family educationÂ model of prenatal which is based on the parent piety as exemplified by Hannah bintÂ Faquz and Prophet Zakariya to his son, the Prohet Yahya. Second, the family educationÂ model of postnatal which has been systematically exemplified by Luqman al-Hakim inÂ educating his son. This Luqman al-Hakim family education model was illustrated fromÂ his testament to his child. The testament is summarized in the following themes suchÂ as: the prohibition to perform shirk; do good to parents and to seek for a role model ofÂ living, to teach shalat and to believe in the Judgment Day, to uphold the principle ofÂ commanding the good and forbidding the evil (amar maâruf nahi munkar), and so on.